Analisis Strategi Marketing Public Relations Dalam Meningkatkan Loyalitas Customer Sofyan Hotel (Studi Deskriptif Pada Sofyan Hotel Cut Meutia Menteng Jakarta Pusat) - Audia Saraswati; Diana Prihadini (LUGAS Jurnal Komunikasi, 2020)
The intense competition in the Indonesian tourism industry and the number of business hotels in Jakarta that offer more modern services and facilities make customers disloyal. In this situation, companies need to make a special strategy to maintain and increase customer loyalty. Based on these problems, this research focuses on the Marketing Public Relations strategy in increasing customer loyalty. This research is qualitative research with a descriptive analysis method, data collection techniques in observation, interviews, documentation, and literature study. This research is the Public Relations of Sofyan Hotel Cut Meutia in carrying out the marketing public relations strategy activities using six of the seven marketing public relations instruments and using the pull, push, and pass strategy according to Kottler and Keller. These include publications in print and online media, identity media, events, news, sponsorship, and corporate social responsibility. The suggestions given in this study to Sofyan Hotel Cut Meutia are maximizing Marketing Public Relations activities by making innovations, improving hotel services and facilities to customers.